PROJECT-BASED LEARNING IN PRIMARY STEM: FOSTERING CRITICAL THINKING AND COLLABORATION THROUGH REAL-WORLD ENVIRONMENTAL CHALLENGES - Alain Morel; Marie Ange Lablache; Richard Padayachy (International Journal of Educatio Elementaria and Psychologia, 2025)
The integration of Project-Based Learning (PBL) into primary STEM education has gained attention as an effective approach for developing critical thinking and collaboration skills among young students. PBL offers an interactive, student-centered learning environment where students engage in real-world challenges, promoting deeper understanding and problem-solving skills. This study explores the impact of PBL on fostering critical thinking and collaboration through real-world environmental challenges in a primary school STEM context. The research aims to examine how PBL influences students’ ability to think critically about environmental issues and work collaboratively to propose sustainable solutions. A mixed-methods approach was employed, involving both quantitative assessments of critical thinking skills and qualitative data from observations and student reflections. The results show a significant improvement in students’ critical thinking abilities, with 85% of students demonstrating enhanced problem-solving skills. Collaboration skills also improved, with 90% of students reporting better teamwork and communication during the project. The study concludes that PBL is an effective pedagogical tool for enhancing both critical thinking and collaboration skills in primary STEM education. These findings suggest that real-world environmental challenges provide a meaningful context for students to engage in active learning, thereby improving their academic and social skills in STEM disciplines.